How to Achieve Conservation Outcomes at Scale: An Evaluation of Scaling Principles - Battista, Willow; Tourgee, Amy; Wu, Candice; Fujita, Rod (Frontiers in Marine Science, 2017)
The importance of scaling initiatives that promote environmental protection and conservation is almost universally recognized. But how is scaling best achieved? We empirically evaluated the relationship of a list of factors that have been postulated to facilitate successful scaling to the degree of scaling success achieved in 56 case studies from a variety of sectors. We identified 23 factors that are significantly associated with successful scaling, defined as self-replication: an innovation that is congruent with local sociocultural patterns, takes advantage of existing scaled infrastructure, and facilitates a paradigm shift; adequate resources and constituencies for scaling, secured from the start, drawn from both within and outside the system; pilot sites that reflect conditions at future sites rather than ideal conditions; clear and deliberate scaling expectations and strategy; capitalization on economies of scale; a project team that has a unifying vision, includes both individuals who helped design the innovation and members of the target audience, and empowers users with the requisite skills; target audiences that take ownership of the project; the provision of long-term support systems; ongoing learning about the factors influencing scaling; direct management of relevant supply and demand streams; targeted marketing and dissemination efforts; and the evaluation of scaling success indicators. We also explored correlations between these principles, and identified a group of principles that together explain nearly 40% of the variance in success: the provision of long-term support systems (or one of its surrogates: turning users into partners, a user organization with wide reach, and the empowerment of the target audience with requisite skills); resources mobilized from within and outside the system; user organizations that have the capacity to implement the innovation; innovations that are platform solutions and that provide rapid feedback; and pilot sites that have realistic conditions relative to future sites. Our results suggest that for scaling to be successful: (1) scaling must be considered at all stages of a project; (2) the context must be managed and barriers to scaling must be identified and removed and (3) deliberate attention must be paid to scaling methods, marketing and dissemination efforts, and long-term monitoring of scaling progress.